Firm Subsidies, Wages and Labor Mobility - Mika Maliranta; Niku Määttänen; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2016)
The bulk of innovation subsidies in Finland are allocated to firms in industries where the employment share of “innovators,” i.e., workers who are specialized in R&D&I, is very high. The average subsidy per employee is typically the highest among young firms. At the firm level, an increase in innovation subsidies is typically associated with an inflow of innovators from high-productivity firms. These findings suggest that innovation subsidies contribute to economic renewal and the diffusion of knowledge between firms. Non-innovation subsidies, in contrast, appear to support established industry structures: a large share of them has been granted to relatively old firms within “traditional” manufacturing industries. Since non-innovation subsidies are systematically allocated to different types of firms than innovation subsidies, they may also crowd out resources from firms that receive innovation subsidies, thereby overriding some of the possible beneficial effects of innovation subsidies.
Keywords: O31; O33; O38; J62; 330; Firm subsidies; Innovation; Productivity; Labor mobility; Forschungsfinanzierung; Industrieforschung; Subvention; Lohnniveau; Arbeitsmobilität; Produktivität; Finnland